MtDNA Haplogroups and Elite Korean Athlete Status - Kim, K. C.; Cho, H. I.; Kim, W. (International Journal of Sports Medicine, 2012)
Mitochondrial DNA (mtDNA) variation has recently been suggested to have an association with athletic performance or physical endurance. Since mtDNA is haploid and lacks recombination, specific mutations in the mtDNA genome associated with human exercise tolerance or intolerance arise and remain in particular genetic backgrounds referred to as haplogroups. To assess the possible contribution of mtDNA haplogroup-specific variants to differences in elite athletic performance, we performed a population-based study of 152 Korean elite athletes [77 sprint/power athletes (SPA) and 75 endurance/middle-power athletes (EMA)] and 265 non-athletic controls (CON). The overall haplogroup distribution of EMA differed significantly from CON (p<0.01), but that of SPA did not. The EMA have an excess of haplogroups M* (OR 4.38, 95% CI 1.63–11.79, p=0.003) and N9 (OR 2.32, 95% CI 0.92–5.81, p=0.042), but a dearth of haplogroup B (OR 0.26, 95% CI 0.09–0.75, p=0.003) compared with the CON. Thus, our data imply that specific mtDNA lineages may provide a significant effect on elite Korean endurance status, although functional studies with larger sample sizes are necessary to further substantiate these findings.
Keywords: mitochondrial DNA; mtDNA haplogroup; physical endurance; association study